Effect of Cement Composition in Lampung on Concrete Strength - Hery Riyanto (International Conference on Engineering and Technology Development (ICETD), 2014)
The strength and durability of concrete depends on the composition of its constituent materials ie fine aggregate, coarse aggregate, cement, water and other additives. The cement composition is about 10% acting as a binder paste material fine and coarse aggregates. In the Lampung market there are several brands of portland cement used by the community to make concrete construction. Although there is a standard of the government of portland cement composition, yet each brand of cement has different characteristics. Cement is generally composed of limestone / limestone containing calcium oxide (CaO), clay (clay) containing silica oxide (SiO2), aluminum oxide (Al2O3), iron oxide (Fe2O3) and a cast that serves to control the hardening. Cement manufacturers make products based on chemical elements resulting from the research to make their products better than other products, so although procedurally similar but have different composition and properties. Another difference are the density, start and end time of bonding and strength. This research will be conducted research on several brands of cement in the province of Lampung, among others, vicat test, the consistency test, compression test and bending in reinforced concrete beam structure. From the research it can be shown the cement test results as an input to the user as a result of the unequal nature of the cement.